Combination of hidrocortisone, kemicitine, lanoline and vaseline for allergic cheilitis treatment: case report: Kombinasi hidrokortison, kemisetin, lanolin, dan vaseline dalam perawatan cheilitis alergika: laporan kasus - Raziy Ganesha; I Nyoman Gede Juwita Putra (Makassar Dental Journal PDGI Makassar, 2022)
Cheilitis is a term to describe inflammation of the vermillion border of the lips. This case report describes compounding with a combination of hydrocortisone,chemicetin, lanolin and vaseline for the treatment of allergic contact cheilitis. Patients with com-plaints of lower lip feeling dry, cracked, sore and bleeding;dryness for 4 days ago. Dry lips getting worse for 2 days ago until bleeding. Objective examination revealed fissures, multiple, well-defined, irregular edges, 1-2 mm long; crusts, regular edges, clear borders, blackish red color; desquamation, multiple, irregular edges, clear boundaries, white color, rough surface. The pa-tient was prescribed a combination of drugs of hydrocortisone, chemicetin, lanoline and vaseline and was instructed on how to use the drug and control it 7 days later. Treatment of allergic contact cheilitis with compounding combination drugs aimed at accelerating healing. However, the success of this case treatment is still based on a proper history so that it chooses a supporting examination and can establish a proper diagnosis.